Deep eutectic solvent dispersive liquid–liquid microextraction methods for the analysis of chlorophyll natural colorant (E140) via microwave assisted sample preparation - Kızıl, Nebiye; Başaran, Erkan; Yola, Mehmet Lütfi; Soylak, Mustafa; Kızıl, Nebiye; Yola, Mehmet Lütfi (Elsevier Inc.)
In the current research paper, extraction and analysis of chlorophyll, one of the bioactive compounds that is usually utilized as natural pigments (E140) and obtained from many leafy green plants and seaweeds, have been carried out via deep eutectic solvent-based dispersive liquid–liquid phase microextraction (DES-UA-DLLME) from plants and food pruducts. The DES-UA-DLLME method was developed by utilizing deep eutectic solvent (DES) which was prepared by heating process with a 1:1 ratio of choline chloride and urea (ChCl: U). Analytical parameters such as pH, DES volume, sample volume, centrifugation and mixing time, DES type, matrix effect, etc. were optimized to ensure the extraction efficiency of chlorophyll. The limit of detection (LOD), limit of quantification (LOQ), intra-day and inter-day relative standart devision (RSD) were found as 0.007 µg/mL, 0.023 µg/mL, 1.3 %, and 1.9 %, respectively. The accuracy of the method was tested with water sample addition/recovery studies. The DES-UA-DLLME method has been applied to food, water, and plant samples. The food products and plants were prepared with the help of ultrasonic and microwave extraction for spectrophotometric analysis of chlorophyll. According to literature survey, the DES-UA-DLLME method and the MWAE method combination was used to the first time for extraction of chlorophyll (E140) from plants. © 2023 Elsevier B.V.
Keywords: Bioactive compounds, E140; Chlorophyll; Deep eutectic solvent; Green chemistry; UV–Vis spectrophotometry